Pelatihan Penerapan Prinsip Personal Hygiene dan Sanitasi Dalam Pengolahan Ikan Asap di Sentra Ikan Asap Kelurahan Hamadi, Kota Jayapura, Papua - Warpur, Maklon; Wanimbo, Efray; Izaac, Fransina A.; Kedebak, Novita; Mantayborbir, Vyona; Agamawan, Lalu Panji Imam; Indrayani, Ervina (JURNAL PENGABDIAN PAPUA, 2025)
The development of tourism and the creative economy in Indonesia can be seen from the increasing number of culinary tours emerging. Regional governments are given the freedom and authority for regions to regulate and utilize their resources to the maximum to produce products and introduce the potential of a region. One product that is quite popular in Jayapura City is smoked fish. The perpetrators of this business are a group of housewives with the aim of increasing income. The quality of processed fish products is the main thing that needs to be maintained starting from the initial selection of raw materials to handling during distribution of the product in question, such as personal hygiene and sanitation during processing. This is an absolute requirement for food processing, because its effect on the quality and food safety of the products produced. The Ikbal Family Fish Processing Unit (UPI) is one of the smoked fish processing units in Jayapura City which is very active in processing smoked fish products. The results of this activity are that group members understand the importance of using personal protective equipment (PPE) in supporting personal hygiene and sanitation in the production of smoked fish, group members are accustomed to using PPE in the production process and group members are proficient in using vacuum sealer packaging tools to maintain the quality of smoked fish.